Long-term exposure to ambient air pollution and cognitive function in older US adults: The Multi-Ethnic Study of Atherosclerosis. Issue 1 (7th February 2023) - Wang, Meng; Zhou, Xiao-Hua Andrew; Curl, Cynthia; Fitzpatrick, Annette; Vedal, Sverre; Kaufman, Joel
Abstract : Background: Air pollution effects on cognitive function have been increasingly recognized. Little is known about the impact of different sources of fine particulate (PM2.5 ). We aim to evaluate the associations between long-term air pollution exposure, including source-specific components in PM2.5, and cognition in older adults. Methods: Cognitive assessment, including the Cognitive Abilities Screening Instrument (CASI), Digit Symbol Coding (DSC), and Digit Span (DS), was completed in 4392 older participants in the United States during 2010–2012. Residence-specific air pollution exposures (i.e., oxides of nitrogen [NO2 /NO x ], PM2.5 and its components: elemental carbon [EC], organic carbon [OC], sulfur [S], and silicon [Si]) were estimated by geo-statistical models. Linear and logistic regression models were used to estimate the associations between each air pollutants metric and cognitive function. Results: An interquartile range (IQR) increase in EC (0.8 μg/m 3 ) and Si (23.1 ng/m 3 ) was associated with −1.27 (95% confidence interval [CI]: −0.09, −2.45) and −0.88 (95% CI: −0.21, −1.54) lower CASI scores in global cognitive function. For each IQR increase in Si, the odds of low cognitive function (LCF) across domains was 1.29 times higher (95% CI: 1.04, 1.60). For other tests, NO X was associated with slower processing speed (DSC: −2.01, 95% CI: −3.50, −0.52) and worse working memory (total DS: −0.4, 95% CI: −0.78, −0.01). No associations were found for PM2.5 and two PM2.5 components (OC and S) with any cognitive function outcomes. Conclusion: Higher exposure to traffic-related air pollutants including both tailpipe (EC and NO x ) and non-tailpipe (Si) species were associated with lower cognitive function in older adults.